Independent and concomitant associations of gestational diabetes and maternal obesity to perinatal outcome: A register-based study - Ijäs, Hilkka (PLoS One, 2019)
AIMS: Gestational diabetes (GDM) is often accompanied by maternal overweight. Our aim was to evaluate the separate and concomitant effects of GDM and maternal overweight/obesity on perinatal outcomes. METHODS: We used the Finnish Medical Birth Register to identify all 24,577 women with a singleton pregnancy who delivered in 2009 in Finland and underwent an oral glucose tolerance test (OGTT). Women were divided into groups according to the result of OGTT (GDM/no GDM) and pre-pregnancy body mass index (BMI): normal weight (≤24.9 kg/m(2)), overweight (25.0–29.9 kg/m(2)), and obese (≥30.0 kg/m(2)). Primary outcomes included macrosomia, caesarean delivery, and treatment at neonatal ward. Normal weight women without GDM constituted the reference group. RESULTS: Compared to reference group, overweight or obese women without GDM had an increased risk of macrosomia [odds ratio adjusted for age, parity, smoking and socio-economic status (aOR)1.18 (95% CI 1.09–1.28) and 1.50 (95% CI 1.19–1.88)], and caesarean delivery [aORs 1.17 (95% CI 1.07–1.28) and 1.52 (95% CI 1.37–1.69)], respectively. In normal weight GDM women the risk of macrosomia [aOR 1.17 (95% CI 0.85–1.62)] and caesarean delivery [aOR 1.10 (95% CI 0.96–1.27)] was not significantly increased as compared to normal weight women without GDM. GDM increased the risk of treatment at neonatal ward in all BMI categories and maternal obesity without GDM was also a risk factor for treatment at neonatal ward. Interaction p values between BMI and GDM on these outcomes were <0.001. CONCLUSIONS: Maternal overweight and obesity without GDM increased the risk of macrosomia and caesarean delivery when compared to the reference group. These risks were amplified when overweight/obesity was accompanied by GDM. Obesity without GDM was a risk factor for treatment at neonatal ward; GDM increased this risk in all BMI categories. Our results suggest that especially maternal obesity should be considered as a risk factor for adverse pregnancy outcomes and GDM further amplifies this risk.